Social Media and Cyberbullying Behavior: (Case Study at SMA Negeri 6 Tangerang) - Firmansyah, Kevin Chelsea; Basit, Abdul (Jurusan Ilmu Komunikasi UTM, 2024)
Social media was created to enable people to communicate with each other without the limitations of distance, place, or time. However, irresponsible use, especially among teenagers under the age of 17, can lead to negative effects such as online harassment. Using social cognitive theory, this research aims to investigate the relationship between the intensity of social media use and cyberbullying behavior among students of SMA Negeri 6 Tangerang. Quantitative methods were used; social media was used as the independent variable and cyberbullying behavior as the dependent variable. Data were collected using the simple random sampling technique through questionnaires distributed to 38 students. A significant relationship between the two variables was found through data analysis using the product moment correlation test (r = 0.754; p 0.05). The research results indicate that the frequency of social media use leads to more cyberbullying behavior due to the disinhibition effect, which gives people the freedom to express their aggression online. In the real world, this research emphasizes the importance of teaching students digital literacy; it is crucial for parents and educators to monitor their social media usage; and to create comprehensive policies to prevent cyberbullying.